The Effect of Deep Breath Relaxation Techniques on Pain of Labor Phase 1 Active Phase in Mothers Mability at Kolonodale Hospital North Morowali Regency - Sesilia Tandondo, Hana; Yulianti, Yulianti; Irmayanti, Irmayanti (Literasi Indonesia Emas (PT), 2025)
Background: One of the fundamental efforts to reduce maternal mortality rate (MMR) is to minimize labor pain experienced by the mother. Labor pain can be managed through two methods: pharmacological and non-pharmacological. Pharmacological methods, which use chemical drugs, are often more expensive and may have adverse effects on both the mother and fetus. In contrast, non-pharmacological methods, such as relaxation techniques, are simpler, cheaper, and more effective, with no side effects. Objective: The purpose of this study was to determine the effect of breath relaxation techniques in reducing labor pain during the active phase I. Method: This research employed a quasi-experimental design with a one-group pretest and posttest approach. The study population consisted of 31 respondents selected through total sampling. Data were collected using a questionnaire, and data analysis was performed using the Wilcoxon statistical test with a significance level of α = 0.05. Results: Almost all respondents experienced a decrease in pain scale after being given the deep breathing relaxation method. Analysis of the Wilcoxon test results showed a P-value of <0.001, which is less than 0.05, indicating a significant effect of the deep breathing relaxation technique on reducing labor pain. Conclusion: The study concluded that the deep breathing relaxation technique significantly decreased the intensity of pain felt by women in the first active phase of labor.